The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1191/0269215505cr805oa
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation of oxygen consumption and gait pattern in amputees using Intelligent Prostheses and conventionally damped knee swing-phase control

Abstract: At lower speeds oxygen cost was lower with the Intelligent Prosthesis. Gait analysis detected no significant changes between the two legs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 10 publications
0
72
1
2
Order By: Relevance
“…Although IP users still demonstrated increased energy expenditure compared with the nondisabled subjects, the 24 percent increase was less than previously documented for TF amputees. Datta et al recently compared conventional and microprocessor-controlled knees in amputees at several walking speeds and found significantly reduced oxygen costs at slower walking speeds; however, they did not calculate net oxygen costs and none of the subjects reached steady state at any of the speeds [9]. Subtraction of the subjects' oxygen cost at rest from the oxygen cost at slower walking speeds might have eliminated the statistically significant difference at slower walking speeds observed by Datta et al [9].…”
Section: Introductionmentioning
confidence: 93%
“…Although IP users still demonstrated increased energy expenditure compared with the nondisabled subjects, the 24 percent increase was less than previously documented for TF amputees. Datta et al recently compared conventional and microprocessor-controlled knees in amputees at several walking speeds and found significantly reduced oxygen costs at slower walking speeds; however, they did not calculate net oxygen costs and none of the subjects reached steady state at any of the speeds [9]. Subtraction of the subjects' oxygen cost at rest from the oxygen cost at slower walking speeds might have eliminated the statistically significant difference at slower walking speeds observed by Datta et al [9].…”
Section: Introductionmentioning
confidence: 93%
“…Several studies have compared various outcomes associated with use of MKMs versus nonmicroprocessor knee mechanisms (NMKMs) [8][9][10][11][12][13][14][15]. In a within-subject study of 12 TF amputees, Schmalz et al reported a 6 percent reduction in oxygen consumption rate (milliliter/ kilogram/minute) at slower walking speeds for the C-Leg versus an NMKM [8].…”
Section: Walking Testsmentioning
confidence: 99%
“…Therefore, it can be stated that microcontrolled intelligent prostheses improve damping performance as a function of the stride velocity transition, with a reduction in oxygen consumption during walking, over a wide range of velocities (Datta et al, 2005;Johansson et al, 2005;Kahle et al, 2008;Schmalz et al, 2002;Taylor et al, 1996).…”
Section: Introductionmentioning
confidence: 99%